Congratulations to Dr. Pennell - (:unkn) unknown (Coy C. Carpenter Library, 1992)
Published in: Medical Alumni News.
Dr. Timothy C. Pennell graduated from Bowman Gray School of Medicine in 1960 and joined the medical school faculty in 1966. In this 1992 photo he was honored for the third time in his career by having the school's yearbook, The Gray Matter, dedicated to him. Dr. Pennell at the time was chief of professional services for North Carolina Baptist Hospital and was director of Bowman Gray's Office of International Health Affairs since its inception in 1984. He was very instrumental in developing academic affiliations between Bowman Gray and medical schools in Japan, China, Italy and Norway. Dr. Pennell was also active with medical professionals in Africa, Asia and South America.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth